ATLAS operasi ilmu bedah saraf: pendarahan epidural & fraktun kompresi tengkorak/ M. Zafrullah Arifin.[et.al]. - Zafrullah Arifin M.; Genis Ginanjar (Sagung Seto, 2012)
V, 119hlm.: ilus.; 21cm.(3 eks)